Highly stable and ordered intermetallic PtCo alloy catalyst supported on graphitized carbon containing Co@CN for oxygen reduction reaction - Jung, Won Suk; Lee, Woong Hee; Oh, Hyung-Suk; Popov, Branko N. (ROYAL SOC CHEMISTRY, 2020)
A PtCo alloy catalyst was prepared by thermal diffusion of Co encapsulated with thin N-doped carbon layers on graphitic carbon into a Pt lattice (PtCo/NGC). The Co diffused up to the near-Pt surface and resulted in an intermetallic PtCo structure without the leaching process. The intermetallic PtCo structure thermally treated under optimized conditions showed 3-fold higher mass activity than the commercial Pt/C. The potential and maximum power density loss of PtCo/NGC after 30 000 potential cycles were 34 mV and 11%, respectively, which indicated that the PtCo/NGC was remarkably stable when compared to commercial Pt/C and commercial PtCo/GC catalysts. The enhanced catalytic performance and stability of the PtCo/NGC catalyst were attributed to the formation of an intermetallic structure that alleviated the Pt oxidation and Co dissolution. The outstanding performance and stability qualify the ordered intermetallic PtCo/NGC to be a promising cathode catalyst for the commercialization of fuel cells.
Keywords: ONE-POT SYNTHESIS; CATHODE CATALYSTS; PLATINUM DISSOLUTION; SURFACE-COMPOSITION; TRANSITION-METALS; PARTICLE-SIZE; NITROGEN; NANOPARTICLES; ELECTROCATALYSIS; PERFORMANCE